INCREASED PREVALENCE OF ANXIETY IN HOSPITALIZED CROHN'S DISEASE PATIENTS IN THE UNITED STATES: INSIGHTS FROM NATIONAL INPATIENT DATABASE FROM 2009 TO 2018. (22nd January 2022) - Bhurwal, Abhishek; Mutneja, Hemant; Pimpinelli, Sophia; Pimpinelli, Marcella; Seril, Darren
Abstract: BACKGROUND: Patients with Crohn's disease (CD) are at increased risk of developing anxiety and depression, and there is growing evidence that these patients would benefit from mental health screening. This study aimed to examine the temporal trends of anxiety and depression diagnoses in hospitalized CD patients in the United States. METHODS: Using the National Inpatient Database (NIS) for the years 2009 to 2018, we analyzed all admissions for CD-related discharges using ICD 9 and ICD 10 CM codes. Besides the primary discharge diagnosis of CD, we also included discharges with a primary complication of CD or with a secondary diagnosis of CD. ICD CM codes were also utilized to identify associated comorbidities of depression and anxiety. Subsequently, we analyzed (1) the overall prevalence of depression and anxiety for CD related admissions, and (2) national temporal trends for depression and anxiety in hospitalized CD patients, from 2009 to 2018. All statistical analyses were performed using STATA software. RESULTS: Using the NIS cohort for the years 2009 to 2018, a total of 585, 867 CD-related discharges were identified. Overall, the prevalence of anxiety amongst CD-related admissions was 15.3%, and the prevalence of depression was 16.5%. The prevalence rate of anxiety increased from 7.7% in 2009 to 22.21% in 2018 (p<0.001). The prevalence of depression increased from 14.8% in 2009 to 17.3% in 2018 (p=0.15) (see Figure 1). CONCLUSION: These results obtained utilizing the NIS indicate that the prevalence of psychiatric diagnosis, particularly anxiety, increased in hospitalized CD patients over time. The diagnosis of anxiety increased 3-fold during the time period studied. The prevalence of anxiety and depression have been reported to be higher in CD patients than in the general population. This study highlights the importance of incorporating psychological screening and mental health services in the management CD patients in both the outpatient and inpatient settings. Further studies are needed to examine the cause of the increased anxiety and depression rates observed in this patient population.